PENERAPAN MEDIA SOSIAL UNTUK PENINGKATAN PEMASARAN PRODUK UMKM MAKANAN RINGAN - Farha, Istiqomah Naziyah; Utami, Evi Tri; Umma, Hanisatul; Winata, Fikri Alif; Masruroh, Rohmah Umi; Putri, Maylina Jasmine Harsindra; Oktavia, Maulia Nur; Nugraha, Kresna Raihan; Sitompul, Nicolaudina Ruthnauli Jasmine; Sitorsmi, Mumpuni Wahyudiarti (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study examines the implementation of digital marketing for MSME products, especially snacks in Sidosari Village, Salaman Sub-district, Magelang District. This research uses a qualitative approach through interviews and observations with 15 MSME players. This study aims to identify barriers to the use of digital marketing, analyze the potential of digital markets, and formulate effective marketing strategies. The results revealed that digital marketing expands market reach, marketing cost efficiency, and increased interaction with consumers. However, MSMEs in Sidosari Village face several challenges such as limited digital skills, difficulty accessing the internet, limited capital, and high competition among sellers. Further analysis shows that almost all MSME players in Sidosari Village still rely on conventional marketing methods. Based on these findings, this study recommends a digital marketing strategy that suits the needs of MSMEs, including digital skills training and social media. The research emphasizes the importance of government and stakeholder support in building a good digital ecosystem, including the provision of internet infrastructure and digital empowerment programs.